74 A POTENTIAL ROLE FOR 5-LIPOXYGENASE IN THE PATHOGENESIS OF CEREBELLAR DYSFUNCTION IN SYSTEMIC LUPUS ERYTHEMATOSUS. (1st March 2006) - Ostmann, O.; Santoro, T. J.; Tomita, M.
Abstract : Systemic lupus erythematosus (SLE) is an autoimmune disease of unknown etiology associated with inflammation involving the lungs, kidneys, joints, skin, and brain. Central nervous system (CNS) involvement in human and experimental SLE is characterized, in part, by disturbances in posture, balance, and tremulousness, which map to the cerebellum (J Neurosci Res 2001;64:26). Five-lipoxygenase (5-LO) activity is increased in the setting of neurodegeneration associated with aging, ischemia, and other CNS insults, which may be accompanied by cerebellar dysfunction. To determine whether 5-LO contributes to CNS inflammation/neurodegeneration in neuropsychiatric lupus, we studied 5-LO and 5-LO activating protein (FLAP) in the cerebellum of MRL- lpr/lpr mice, which spontaneously develop a lupus-like illness associated with disturbances in cerebellar function. Relative to age- and sex-matched, immunologically and neurologically normal, H-2 identical CBA/CaJ mice, cerebellar homogenates from 20- to 30-week-old clinically affected MRL- lpr/lpr mice exhibited enhanced expression of genes encoding both 5-LO and FLAP as assessed by reverse transcriptase polymerase chain amplification. In contrast, no differences were found in the expression of genes encoding cytosolic phospholipase A2 and neuronal nitric oxide synthase in the cerebellum of autoimmune and control mice. Western blotting of homogenates indicated that MRL- lpr/lpr mice had a greater content of 5-LO but not of FLAP protein compared with control CBA/CaJ mice. These data suggest a potential role for 5-LO in the pathophysiology of cerebellar dysfunction in lupus.